Motivating Training Transfer Among UITM Academic Staff at the Institute of Leadership and Development - Sarina Nik Md Salleh, Nik; Amin, Aziz; Mamat, Ibrahim (International Journal of Engineering and Technology, 2018)
Previous empirical studies have highlighted the failure of training transfer among employees, regardless of job sectors. Thus, this study examined the associations between employee readiness, training design, work environment and transfer of training among the academic staff of UiTM. This study also aimed to determine if transfer motivation mediates the associations between employee readiness, training design, work environment and training transfer. A quantitative and questionnaire survey method was employed in this study. A total of 258 academic staff of UiTM as participants of training courses at Institute of Leadership and Development (ILD), UiTM were selected and notified through e-mail to participate in an online survey. 238 responses were received and found usable for the final analysis. The results found that among the employee readiness, design of training and work environment factor, abilities, supervisor’s role, error management, and opportunity to use had significant and positive relationships with transfer of training Moreover, the study confirmed the intervening effects of transfer motivation on the relationships between opportunity to use, error management and training transfer. Overall, the study had successfully developed a model of training transfer for UiTM’s academic staff which was influenced by abilities, supervisor’s role, error management, and opportunity to use.